Epigenetics in Metastatic Breast Cancer: Its Regulation and Implications in Diagnosis, Prognosis and Therapeutics - Wu, Yuan S.; Lee, Zhong Yang; Chuah, Lay-Hong; Mai, Chun Wai; Ngai, Siew Ching (Current Cancer Drug Targets, 2019)
Despite advances in the treatment regimen, the high incidence rate of breast cancer (BC) deaths is mostly caused by metastasis. Recently, the aberrant epigenetic modifications, which involve DNA methylation, histone modifications and microRNA (miRNA) regulations become attractive targets to treat metastatic breast cancer (MBC). In this review, the epigenetic alterations of DNA methylation, histone modifications and miRNA regulations in regulating MBC are discussed. The preclinical and clinical trials of epigenetic drugs such as the inhibitor of DNA methyltransferase (DNMTi) and the inhibitor of histone deacetylase (HDACi), as a single or combined regimen with other epigenetic drug or standard chemotherapy drug to treat MBCs are discussed. The combined regimen of epigenetic drugs or with standard chemotherapy drugs enhance the therapeutic effect against MBC. Evidences that epigenetic changes could have implications in diagnosis, prognosis and therapeutics for MBC are also presented. Several genes have been identified as potential epigenetic biomarkers for diagnosis and prognosis, as well as therapeutic targets for MBC. Endeavors in clinical trials of epigenetic drugs against MBC should be continued although limited success has been achieved. Future discovery of epigenetic drugs from natural resources would be an attractive natural treatment regimen for MBC. Further research is warranted in translating research into clinical practice with the ultimate goal of treating MBC by epigenetic therapy in the near future.
Keywords: histone deacetylation